Atomic Force Microscopy (AFM) Analysis of an Object Larger and Sharper than the AFM Tip. (October 2019) - Chen, Zhe; Luo, Jiawei; Doudevski, Ivo; Erten, Sema; Kim, Seong H.
Abstract: Atomic force microscopy (AFM) is typically used for analysis of relatively flat surfaces with topographic features smaller than the height of the AFM tip. On flat surfaces, it is relatively easy to find the object of interest and deconvolute imaging artifacts resulting from the finite size of the AFM tip. In contrast, AFM imaging of three-dimensional objects much larger than the AFM tip height is rarely attempted although it could provide topographic information that is not readily available from two-dimensional imaging, such as scanning electron microscopy. In this paper, we report AFM measurements of a vertically-mounted razor blade, which is taller and sharper than the AFM tip. In this case, the AFM height data, except for the data collected around the cutting edge of the blade, reflect the shape of the AFM tip. The height data around the apex area are effectively the convolution of the AFM tip and the blade cutting edge. Based on computer simulations mimicking an AFM tip scanning across a round sample, a simple algorithm is proposed to deconvolute the AFM height data of an object taller and sharper than the AFM tip and estimate its effective curvature.